Antifungal effect of the essential oil from leaves and stems of schinus molle over aspergillus sp. - de Menezes Filho, Antonio Carlos Pereira; de Sousa, Wendel Cruvinel; de Oliveira Filho, Josemar Gonçalves [UNESP]; de Souza Castro, Carlos Frederico (My University, 2020)
Introduction: Aspergillus is a group of phytopathology and pathologic microorganisms that are found all over the world. Objective: To assess the antifungal activity of the essential oils from the leaves and stems of Schinus molle in stumps of Aspergillus flavus, Aspergillus niger and Aspergillus fumigatus in Rio Verde, Goiás, Brazil. Methods: Leaves and stems of Schinus molle were collected in the night. The essential oils were extracted by hydrodistillation and the assessment of fungi was made in different concentrations of fluid essential oil. Results: Both essential oils showed important antifungal activity against the three assessed stumps of Aspergillus. Conclusions: Essential oils of S. molle have a high efficiency in the inhibition of growing in A. flavus, A. niger and medium efficiency in A. fumigatus in in vitro trials in different concentrations of essential oil from the leaves and the stems. Therefore, there must be more work in the assessment of this fungistatic behaviour in hothouses, in the fields and in animal models, since this antifungal activity might represent the genesis of new sources for the production of antifungal agents with agricultural and pharmaceutical uses.
Efecto antifúngico por el aceite esencial de las hojas y tallos de schinus molle sobre aspergillus sp.
Keywords: Antifungical activity; Aspergillosis; Aspergillus genre; Schinus genre